Galectin-3 reflects the echocardiographic quantification of right ventricular failure. (1st December 2021) - Ansari, Uzair; Behnes, Michael; Hoffmann, Julia; Weidner, Kathrin; Kuche, Philip; Rusnak, Jonas; Kim, Seung-Hyun; Natale, Michele; Reckord, Nadine; Lang, Siegfried; Hoffmann, Ursula; Bertsch, Thomas; et al.
Abstract: Objectives . Galectin-3 (gal-3) is a mediator of extracellular matrix metabolism and reflects an ongoing cardiac fibrotic process. The aim of this study was to determine the potential use of gal-3 in evaluating the structural and functional parameters of the right ventricle as determined by echocardiography. Design. Ninety-one patients undergoing routine echocardiography were prospectively enrolled in this monocentric study. Serum samples for gal-3 and aminoterminal pro-brain natriuretic peptide (NT-proBNP) were collected within 24 h of echocardiographic examination. Patients were arbitrarily divided into subgroups based on right ventricular function as measured by tricuspid annular plane systolic excursion (TAPSE) and these included TAPSE >24 mm ( n  = 23); TAPSE 18–24 mm ( n  = 55); TAPSE ≤17 mm ( n  = 13); permitting the detailed statistical analysis of derived data. Results. Serum levels of gal-3 in all patients correlated with age ( r  = 0.36. p  < .001), creatinine ( r  = 0.60, p  < .001), NT-proBNP ( r  = 0.53, p  < .001), RA area ( r  = 0.38, p  < .001) and TAPSE ( r = −0.3. p  < .01). The distribution of echocardiographic indices according to TAPSE subgroups revealed an association between gal-3 and its ability to identify patients with right ventricular failure (RVF) as diagnosed by a TAPSE ≤17 mm ( r  = 0.04, p  < .001). The multivariable logistic regression model with adjusted odds ratio showed the ability of gal-3 to identify RVF when adjusted to age and gender (adjusted odds ratio 3.60, 95% CI 1.055–12.282, p  < .05). Conclusion. Gal-3 correlated with echocardiographic indices of RVF and could effectively diagnose these patients. The supplementary use of NT-proBNP strengthened the diagnostic capability of each biomarker. Trial Registration: The 'Cardiovascular Imaging and Biomarker Analyses' (CIBER Study), clinicaltrials.gov identifier: NCT03074253. Registered 3/8/2017. https://www.clinicaltrials.gov/ct2/show/NCT03074253